U.S. vaccine and immune globulin product shortages, 2001-15 - Ziesenitz, Victoria C. (AJHP, 2017)
Purpose Trends in shortages of vaccines and immune globulin products from 2001 through 2015 in the United States are described. - Methods Drug shortage data from January 2001 through December 2015 were obtained from the University of Utah Drug Information Service. Shortage data for vaccines and immune globulins were analyzed, focusing on the type of product, reason for shortage, shortage duration, shortages requiring vaccine deferral, and whether the drug was a single-source product. Inclusion of the product into the pediatric vaccination schedule was also noted. - Results Of the 2,080 reported drug shortages, 59 (2.8%) were for vaccines and immune globulin products. Of those, 2 shortages (3%) remained active at the end of the study period. The median shortage duration was 16.8 months. The most common products on shortage were viral vaccines (58%), especially hepatitis A, hepatitis B, rabies, and varicella vaccines (4 shortages each). A vaccine deferral was required for 21 shortages (36%), and single-source products were on shortage 30 times (51%). The most common reason for shortage was manufacturing problems (51%), followed by supply-and-demand issues (7%). Thirty shortages (51%) were for products on the pediatric schedule, with a median duration of 21.7 months. - Conclusion Drug shortages of vaccines and immune globulin products accounted for only 2.8% of reported drug shortages within a 15-year period, but about half of these shortages involved products on the pediatric vaccination schedule, which may have significant public health implications.
Gesehen am 17.08.2018